2020
DOI: 10.1016/j.xplc.2020.100116
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Based Trait Differentiation but Lack of Trade-offs between Stress Tolerance and Performance in Introduced Canada Thistle

Abstract: Trade-offs between performance and tolerance of abiotic and biotic stress have been proposed to explain both the success of invasive species and frequently observed size differences between native and introduced populations. Canada thistle seeds collected from across the introduced North American and the native European range were grown in benign and stressful conditions (nutrient stress, shading, simulated herbivory, drought, and mowing), to evaluate whether native and introduced individuals differ in perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…We found that the climatic conditions at the collecting sites were significantly associated with resistance traits in both common gardens, but only for plants from the native range, whereas for plants from the introduced range there were only very few significant associations. Many previous studies of invasive plants have documented the development of parallel clinal patterns in ecological traits among populations of native and introduced ranges (Agrawal et al ., 2015; Leger & Rice, 2007; Etterson et al ., 2008; Rosche et al ., 2019; Hodgins et al ., 2020) and have usually interpreted this as evidence for rapid post-invasion evolution and adaptation. However, there are also studies of successful invasive plants with unparalleled (Bhattarai et al ., 2017; Yang et al ., 2021; Woods & Sultan, 2022) or no clinal patterns at all (Endriss et al ., 2018; Sun & Roderick, 2019), and our results also provide little evidence for post-invasion genetic differentiation of introduced European or North American populations in relation to climate.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the climatic conditions at the collecting sites were significantly associated with resistance traits in both common gardens, but only for plants from the native range, whereas for plants from the introduced range there were only very few significant associations. Many previous studies of invasive plants have documented the development of parallel clinal patterns in ecological traits among populations of native and introduced ranges (Agrawal et al ., 2015; Leger & Rice, 2007; Etterson et al ., 2008; Rosche et al ., 2019; Hodgins et al ., 2020) and have usually interpreted this as evidence for rapid post-invasion evolution and adaptation. However, there are also studies of successful invasive plants with unparalleled (Bhattarai et al ., 2017; Yang et al ., 2021; Woods & Sultan, 2022) or no clinal patterns at all (Endriss et al ., 2018; Sun & Roderick, 2019), and our results also provide little evidence for post-invasion genetic differentiation of introduced European or North American populations in relation to climate.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) assessed the impact of demographic processes on genomic diversity and positive selection in Arabidopsis lyrata by analyzing re-sequencing data from 52 populations collected worldwide. Vaidya and Stinchcombe (2020) used the Medicago truncatula - Ensifer meliloti system to demonstrate that genotype-by-environment interactions make a significant contribution to maintaining genetic variation in mutualisms, and Hodgins et al. (2020) found that invasive populations of Canada thistle show rapid adaptation with no trade-off between stress tolerance and performance.…”
mentioning
confidence: 99%
“…A widely held explanation for this pattern, as well as for the overall success of the invaders, is that invasive plants trade off tolerance to abiotic and biotic stresses for increased performance. In this issue, Hodgins et al. (2020) investigate this hypothesis in the noxious weed, Canada thistle ( Cirsium arvense ), which is native to Eurasia, but has invaded all other continents except Antarctica.…”
mentioning
confidence: 99%